Acute physiological and psychophysical responses to different modes of heat stress - Campbell, H. A.; Akerman, A. P.; Kissling, L. S.; Prout, J. R.; Gibbons, T. D.; Thomas, K. N.; Cotter, J. D. (Experimental Physiology, 2022)
New Findings